Validation of a scale of attitudes towards the math - Hurtado Mondoñedo, Luis (2014)
In order to have an instrument that allows information on attitudes toward mathematics of students in their first three cycles of the University of the Pacific was valited a scale which we called EAMUP scale. This scale was adapted to the scale of Auzmendi applied to high school students. This paper presents the steps taken for validation and provides the data to demonstrate their reliability and validity.